The effect of polishing agents on the transverse strength of heat cured acrylic resin bases - Suraskurmar, Tiysha; Syafrinani, Syafrinani (Indonesian Journal of Prosthodontic, 2020)
Introduction: Heat cured acrylic resin is frequently used denture base material whereby transverse strength is one of the mechanical properties that must be observed. A rough surface absorbs water, reduces strength of denture bases, thus polishing should be done. Pumice is the most abrasive material used in dentistry. Eggshell and tooth-paste can be used as alternative abrasive materials. This study aims to determine the differences in value of trans-verse strength of HCA resin once polished using pumice, eggshells, and toothpaste. Method: This laboratory ex-perimental study using sample sized 65x10x2.5 mm with 30 samples in total for 3 groups. Transverse strength was measured using Universal Testing Machine. The data were analyzed using one-way Anova. Result: The comparison ratio of transverse strength between HCA resin after polishing with pumice, eggshells and tooth paste is 93.63 : 118.42 : 105.91 MPa. It shows there were significant differences in transverse strength between groups with sig-nificant value p was 0.001 which less than 0.05. Conclusion: The value of transverse strength varies according to polishing material used. Eggshell has the highest transverse strength value compared to pumice and toothpaste.